Translating, Adapting and Validating the Revised MISSCARE Survey for Use in Norwegian Hospitals—A Pilot Study - Kjersti Grønning PhD; Melliane Muteba Olsen MSc; Beate André PhD (SAGE Open Nursing)
Background The original MISSCARE Survey was developed in the US in the early 2000s to assess the amount of missed nursing care. Because additional causes of missed care were detected in later years, the MISSCARE Survey was further developed in 2019 by adding one item in Part A and five items in Part B to the questionnaire. Neither the original nor the revised MISSCARE Survey is translated into Norwegian, so a questionnaire is needed to assess missed nursing care in Norway. This study aims to translate and adapt the revised MISSCARE Survey for use in Norwegian hospitals. Methods A forward translation, followed by an expert panel's back-translation, cognitive interviews, and final version testing were conducted. Exploratory factor analyses were conducted to investigate the underlying factor structure. Internal consistency was assessed using Cronbach's alpha, and the intraclass correlation coefficient (ICC) was employed for a test–retest evaluation. IBM SPSS Statistics (version 29) was used for all analyses. Results A total of 120 nurses and nursing assistants took part in the study assessing the psychometric properties of the Norwegian adaptation of the revised MISSCARE Survey . The exploratory factor analysis for Part B revealed four factors, the Kaiser–Meyer–Olkin measure of sampling adequacy was 0.895, and Cronbach's alpha values ranged from 0.841 to 0.751, reflecting good internal consistency. The overall test–retest ICC was 0.894 for Part A and 0.827 for Part B, indicating strong reliability. Conclusions The revised MISSCARE Survey adapted for use in Norwegian hospitals is a reliable and promising instrument for assessing missed nursing care in medical and surgical units within a local Norwegian hospital. However, further studies should be conducted to confirm the factor structure in larger and more diverse populations.